Pterostilbene mitigates the senescence of human dermal fibroblast cells by enhancing mitochondrial quality - Zhou, Xinyu; Wang, Ning; Wei, Jihua; Li, Guizhi; Lue, Zhengwei; Liu, Chang; Bao, Qi; Feng, Zhe; Zhang, Minjie; Huang, Hu; Li, Yue; Wang, Jing; et al. (Frontiers in Pharmacology, 2025)
IntroductionPterostilbene (PT), a natural polyphenol found in blueberries and several grape varieties, exhibits pleotropic pharmacological effects. PT reduced the makers of aging caused by either ultraviolet (UV) light exposure or chemical stress in keratinocytes, whereas its potential anti-aging effects and underlying mechanisms in the dermis have not been elucidated.MethodsThe anti-senescence effects of PT were investigated in human dermal fibroblasts (HDFs) using models of UVB-induced acute oxidative stress and replicative senescence. Key assays included senescence-associated beta-galactosidase (SA-β-gal) activity, RT-PCR, western blotting, immunofluorescence, live-cell confocal imaging with fluorescent probes, flow cytometry and mitochondrial respiration analysis. A mouse model of UVB-induced skin damage was used to evaluate PT’s anti-aging effects in vivo through histopathological examination and western blot analysis.ResultsPT treatment mitigated senescence in HDFs, as shown by reduced SA-β-gal activity, p16, and p21, along with increased collagen expression. It restored mitochondrial morphology, MMP, and reduced mitochondrial reactive oxygen species in both senescent models. Furthermore, PT improved mitochondrial basal respiration, ATP production, and maximal respiration. Mechanistically, PT promoted mitophagy, indicated by enhanced TOM20/LC3 colocalization. In vivo, topical PT restored collagen, dermal thickness, and LC3, while reducing p21 levels in UVB-exposed mice.DiscussionOur findings demonstrate that PT delays dermal senescence by enhancing mitochondrial quality via enhancing mitophagy. These results highlight PT as a promising anti-aging agent capable of countering both intrinsic and extrinsic aging in the dermis.